Characterizing global citizenship education in U.S. international student services office websites: A critical discourse analysis - Terogo, Ionell Jay R.; Weng, Yun-Han (Journal of International Students, 2026)
This study critically examines how U.S. International Student Services Offices (ISSOs) represent Global Citizenship Education (GCEd) on their websites. Employing critical discourse analysis, it explores the discursive strategies used to foster global citizenship among international students. The analysis identifies four key themes: (1) emphasis on “Living in the U.S.”, (2) neutrality toward global political issues, (3) absence of explicit GCEd spaces, and (4) inconsistencies in vision and mission statements. Findings suggest that ISSOs often promote a U.S.-centric, neoliberal, and implicitly colonial framing of GCEd, which may limit the transformative potential of global citizenship. The study proposes a framework of four levels of GCEd engagement as reflected in ISSO communications. It argues that higher education institutions must strive for deeper, more critical engagement with global issues if they are to genuinely cultivate global citizenship as an institutional goal in higher education internationalization.